2007
DOI: 10.1029/2006jd008074
|View full text |Cite
|
Sign up to set email alerts
|

Scattering matrix of large Saharan dust particles: Experiments and computations

Abstract: [1] We present measurements of the complete scattering matrix as a function of the scattering angle of a sample of Sahara sand particles collected from a dune in Libya. The measurements were performed at a wavelength of 632.8 nm in the scattering angle range from 4°to 174°. To facilitate the use of the experimental data for multiple-scattering calculations with polarization included, we present a synthetic scattering matrix based on the measurements and defined in the full angle range from 0°to 180°. The Libya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 47 publications
2
79
0
Order By: Relevance
“…It was found that g depends on m monotonically and fairly linearly over a wide range of refractive indices. For individual, scattering-angle dependent phase matrix elements the situation is bound to be more complicated, but luckily the angular forms of the matrix elements do not seem to be overly sensitive to fairly modest variations in m (e.g., Nousiainen and Vermeulen, 2003;Muñoz et al, 2007). We are thus confident that, to a large extent, we also cover the single-scattering properties in our treatment.…”
Section: Robustness Of Model With Respect To Refractive Indexmentioning
confidence: 84%
“…It was found that g depends on m monotonically and fairly linearly over a wide range of refractive indices. For individual, scattering-angle dependent phase matrix elements the situation is bound to be more complicated, but luckily the angular forms of the matrix elements do not seem to be overly sensitive to fairly modest variations in m (e.g., Nousiainen and Vermeulen, 2003;Muñoz et al, 2007). We are thus confident that, to a large extent, we also cover the single-scattering properties in our treatment.…”
Section: Robustness Of Model With Respect To Refractive Indexmentioning
confidence: 84%
“…The rationale for this approach, which is similar to that used by Liu et al (2003) and Muñoz et al (2007), is that the forward scattering peak results mainly from the diffraction of the incident light. The strength of the diffraction peak and its scattering angle dependence appears to depend mainly on the size of the particles and fairly shape independent for projected-surface-area equivalent convex particles in random orientation .…”
Section: The Auxiliary Scattering Matrixmentioning
confidence: 99%
“…In this article, we use a method similar to that of Liu et al (2003), that was also used by e.g. Muñoz et al (2007), but we extend this by using expansion coefficients which result from a Singular Value Decomposition (SVD) fit to the measurements with generalized spherical functions (Gel'fand et al, 1963;Hovenier and van der Mee, 1983;de Rooij and van der Stap, 1984;Hovenier et al, 2004). With the added artificial data points and the expansion coefficients, we construct a so-called synthetic scattering matrix, which is normalized so that the average of the synthetic phase function over all directions equals unity and covers the whole scattering angle range (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…1.7 to 1.8 that beg for explanation. In an effort to replicate theoretically the scattering from dusts Zubko has used DDA to calculate the scattering by four types of irregularly shaped particles which he calls pocked spheres, rough surface spheres, strongly damaged spheres and agglomerated debris at three different relevant refractive indices [35]. In collaboration with Zubko we have found once again that Q-space analysis of all nearly all these situations shows power laws [14].…”
Section: Dustsmentioning
confidence: 92%
“…Very recently I have applied the Q-space analysis [13] to a well-known data set [34,35] for scattering from desert dusts. An example is given in Fig.…”
Section: Dustsmentioning
confidence: 99%